Generation And Characterization Of Rna Aptamer Against rHuEPO-a By Selex Technology - Marimuthu, Citartan (2014)
Systematic Evolution of Ligands by Exponential Enrichment (SELEX) enables the isolation of aptamer (ssDNA or RNA that possesses high binding affinity and specificity against virtually any target molecules). In this study, a RNA aptamer against recombinant human EPO-alpha (rHuEPO-α) was successfully isolated by SELEX technology. After 11 cycles of SELEX, cloning and sequence analysis showed an appearance of a single major clone constituting the putative RNA aptamer, termed REPORA-6, with a dissociation constant of 25±1 nM.